Mucosal biopsy shows immunologic changes of the colon in patients with early MS. Issue 4 (July 2017) - Moser, Adrian Mathias; Spindelboeck, Walter; Strohmaier, Heimo; Enzinger, Christian; Gattringer, Thomas; Fuchs, Siegrid; Fazekas, Franz; Gorkiewicz, Gregor; Wurm, Philipp; Högenauer, Christoph; Khalil, Michael
Abstract : Objective: To investigate immune cells of the colonic mucosa and fecal short-chain fatty acids (SCFAs) in treatment-naive patients with a clinically isolated syndrome (CIS) or early relapsing MS. Methods: In this cross-sectional proof-of-concept study, we obtained mucosal specimens during ileocolonoscopy from 15 untreated patients with CIS/MS and 10 controls. Mucosal immune cells were analyzed by FACS, and gas chromatography-mass spectrometry measurements of stool samples served to determine SCFA. Results: The number of total dendritic cells (DCs), CD103+ tolerogenic DCs, and CD4+25+127–regulatory T cells (Tregs) was significantly reduced in the distal colon of patients with CIS/MS compared with controls, whereas we found no differences in the proximal colon. The patients' fecal samples also showed a substantially lower content of SCFA and especially lower levels of butyrate and acetate. Conclusions: Our findings indicate a disturbed homeostasis of colonic DCs and Tregs in patients with MS which could be associated with colonic SCFA depletion. Although not implying causality, these findings confirm parallel abnormalities of the gut in MS and warrant further research if modulation of the colonic SCFA profile or the colonic Treg pool can serve to modify the course of MS.